Extracellular electron transfer leading to the biological mediated production of reduced graphene oxide. (October 2020) - Lu, Yue; Zhong, Linrui; Tang, Lin; Wang, Huan; Yang, Zhaohui; Xie, Qingqing; Feng, Haopeng; Jia, Meiying; Fan, Changzheng
Abstract: To explore a green, low-cost, and efficient strategy to synthesis reduced graphene oxide (RGO), the process and mechanism of the graphene oxide (GO) reduction by a model electrochemically active bacteria (EAB), Geobacter sulfurreducens PCA, were studied. In this work, up to 1.0 mg mL −1 of GO was reduced by G. sulfurreducens within 0.5–8 days. ID /IG ratio in reduced product was similar to chemically RGO. After microbial reduction, the peak which corresponded to the reflection of graphene oxide (001) disappeared, while another peak considered as graphite spacing (002) appeared. The peak intensity of typical oxygen function groups, such as carboxyl C–O and >O (epoxide) groups, diminished in bacterially induced RGO comparing to initial GO. Besides, we observed the doping of nitrogen and phosphorus elements in bacterially induced RGO. In a good agreement with that, better electrochemical performance was noticed after GO reduction. As confirmed with differential pulse voltammetry (DPV) and cyclic voltammetry (CV) analysis, the maximum value of peak currents of bacterially induced RGO were significantly higher than those of GO. Our results showed the electron transfer at microbial cell/GO interface promoted the GO reduction, suggesting a broader application of EAB in biological mediated production of RGO. Graphical abstract: Image 1 Highlights: Provided a green chemistry strategy for the biological production of reduced graphene oxide (RGO) by Geobacter . Bacterially induced RGO by Geobacter exhibited a good performance in electrochemical conductivity. The doping of nitrogen and phosphorus elements were observed in the bacterially induced RGO by Geobacter. Extracellular electron transfer at microbial cell/GO interface promoted the graphene oxide (GO) reduction of Geobacter.